Rebel pain treatment in advanced tumors of the uterus - Cabieses M., F. (2015)
The problem of the pathogenesis and treatment of pain caused by advanced cervical carcinoma arises. According to the authors the idea that the pain is caused by lumbar commitment and sacral plexus in its path and not intrapélvico commitment sympathetic pathways is more acceptable. The importance of a careful study of the scalability of the tumor and the presence of complications arising from her notes, as well as a ranking of the severity of pain based on the systematic use of analgesics, in a reasoned supplemented by sedatives. The reasons why we are opposed to the messy use of opioids in patients who may be permanently relieved of their pain surgically noted. The importance of avoiding addiction to narcotics, source of more serious problems than the pain itself states. It supports section beams spinothalamic spinal cord (cordotomy anterolateral), as the surgical method of choice in pain for advanced pelvic cancer, when it is uncontrollable with moderate doses of analgesics and the patient has a good "surgical risk".